1966
DOI: 10.4141/cjss66-024
|View full text |Cite
|
Sign up to set email alerts
|

Differential Performance of Two Barley Varieties to Varying Aluminum Concentrations

Abstract: In a greenhouse experiment, yields of Charlottetown 80 and Herta barley decreased with increasing rates of aluminum applied to a Caribou loam soil. The decline in yield was greater with the Herta variety. At the same time, this variety did not exhibit symptoms of aluminum toxicity as had been encountered on the same soil m field trials.A nutrient solution experiment established that Charlottetown 80 and Herta possessed a differential tolerance to aluminum and indicated that regional barley production problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1969
1969
1994
1994

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Water stress (2,3,4,19,21,25,26,38) and aluminum toxicity (1,5,6,8,16,18,20,28,29,30,31,32) impose major constraints to plant growth in many parts of the world. Aluminum stress effects are particularly serious in sub-surface soils that have a pH below 5.5 and are difficult to lime.…”
Section: Introductionmentioning
confidence: 99%
“…Water stress (2,3,4,19,21,25,26,38) and aluminum toxicity (1,5,6,8,16,18,20,28,29,30,31,32) impose major constraints to plant growth in many parts of the world. Aluminum stress effects are particularly serious in sub-surface soils that have a pH below 5.5 and are difficult to lime.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural studies (Bennet et al, 1985;1986) show that the primary sites of A1 uptake are the peripheral cells of the root cap and mucilagenous secretions around the root. The A1 interferes with the uptake of Ca and Mg and the transport of P and K. Tolerance seems to be associated with decreased uptake of AI and decreased translocation to the tops (McLean and Chaisson, 1966;Foy, 1974;Miranda, 1985). Phosphorus is held in the roots when toxic levels of AI occur possibly as an aluminium phosphate precipitate (McGormick and Borden, 1974), and Rios and Pearson (1964) showed that P could move in roots to a growing point where A1 is limiting growth.…”
Section: Introductionmentioning
confidence: 99%
“…The solution method has proved very satisfactory for determining varietal response of Al, and we have used this procedure for studying the inheritance of AI, response in barley (7). With some modifications, it can be adapted to other crops, 5 and may prove useful for testing the response of crop plants to other chemical factors.…”
Section: Resultsmentioning
confidence: 99%